Using a fuzzy PID controller for the path following of a car-like mobile robot - Talebi Abatari, Hassan; Dehghani Tafti, Abdolreza (2013 First RSI/ISM International Conference on Robotics and Mechatronics (ICRoM), 2013)
In this paper, to design a path following control system for a car-like mobile robot a simple fuzzy PID controller is presented. The proposed controller has better convergence rate in comparison with standard PID controller for robot with any arbitrary initial state. Fuzzy logic is used to tune each parameters of PID controller. It is tested by simulation on kinematics model of a car-like mobile robot using MATLAB robotic toolbox. Simulation results show that the controller has a better performance than standard PID controller.